Hardness Analysis, Hydrogen Test and Welding Size on Seamless Steel Pipes API 5L Gr.X65 PSL2 with Post Weld Heat Treatment (PWHT) - Kurniawan, Pradhana; Darto, Darto; Annaufal, Ubbayu (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2025)
Seamless steel pipes in oil and gas pipeline applications will provide quite high pressure, so the welding process is important in ensuring pipe safety. This study aims to analyze the hardness, hydrogen test and welding size of seamless steel pipes that undergo post weld heat treatment (PWHT) process. The pipe diameter dimension is 6 inches with API 5L Gr.X65 PSL2 type. The experimental method begins with the PWHT process by heating to a temperature of 625 ° C with a holding time of 1 hour 10 minutes then slowly cooled with a cooling rate of 154 ° C / hour. The specimens that underwent PWHT were then analyzed for hardness, hydrogen test and welding size simulation. The hardness results decreased after PWHT at all basic metal, HAZ and center of weld positions. Position 0 ° ranges from 126-174 HRB, position 120 ° produces a value of 122 - 143 HRB and position 270 ° has a value of 133-154 HRB. The decrease in hardness occurs due to the tempering process which reduces residual stress. The pressure generated in the hydrogen test does not exceed the yield strength of the API 5L Gr.X65 PSL2 pipe material, which is 65,300 psi. The maximum weld size simulation results are produced with a value of 6,448 mm and a minimum value of 1,572 mm. The maximum value is used as a reference in welding to produce a safe connection.